Validity and Reliability the Rowland Universal Dementia Assessment Scale in a Sample of Elderly Women - Sousan Salary; Mohammad Reza Shairi; Mohammad Ali Asghari Moghadam (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: The present study aims to investigate the validity and reliability of measuring dementia scale in a sample of elderly women has been reviewed. Methods & Materials: This study is descriptive based on what has been designed in which 310 elderly women were participated in this study out of two ranges of Tehran Kahrisak Prison and Tehran Jahandidegan Institute after being received the consent letter to participate in. In this study, samples were selected as available sampling and four questionnaires were used to collect information which was completed as an interview with elderly women. Information obtained has been analyzed using SPSS software and related statistical methods. Results: Based on research findings, mean age of people under study was 76/86 years and the scale reliability were reviewed in convergence method (Quality of Life and Elderly's Depression Questionnaire) and divergence (The informant Questionnaire on Cognition Decline in Elderly questionnaire and Mine Mental Status Examination (MMSE). Also, scale validity was 0.792 with Cronbach's alpha method and 0.759 with division method and 76.0 with test-retest method. In addition, factor analysis indicates the saturation of this scale of a factor. Conclusion: The results achieved from this above study indicate that this scale has appropriate reliability and validity among elderly women. Therefore, it seems that planning to do this research will be very effective in clinical and complex population.